2020
DOI: 10.1371/journal.pone.0232850
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a novel species in the genus Cupriavidus from a patient with sepsis using whole genome sequencing

Abstract: Whole genome sequencing (WGS) has become an accessible tool in clinical microbiology, and it allowed us to identify a novel Cupriavidus species. We isolated Gram-negative bacillus from the blood of an immunocompromised patient, and phenotypical and molecular identifications were performed. Phenotypic identification discrepancies were noted between the Vitek 2 (bioMé rieux, Marcy-l'É toile, France) and Vitek MS systems (bioMé rieux). Using 16S rRNA gene sequencing, it was impossible to identify the pathogen to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
(51 reference statements)
0
7
0
1
Order By: Relevance
“…Many historical isolates were first identified as 'CDC Group IVc-2' , which was later classified as a Ralstonia species [11], then as Wautersia [12], before finally being transferred to the genus Cupriavidus [13]. Certain Cupriavidus species such as Cupriavidus pauculus are emerging as opportunistic pathogens of interest [14] with multiple case reports of infection in immunocompromised [15][16][17][18][19] and immunocompetent [20][21][22][23] people as well as in those with cystic fibrosis [24][25][26], with evidence of nosocomial transmission [27][28][29]. A comprehensive summary of bacteraemia caused by Cupriavidus species reported that C. pauculus accounted for the vast majority (87 %) of 23 reported cases across different countries [28].…”
Section: Introductionmentioning
confidence: 99%
“…Many historical isolates were first identified as 'CDC Group IVc-2' , which was later classified as a Ralstonia species [11], then as Wautersia [12], before finally being transferred to the genus Cupriavidus [13]. Certain Cupriavidus species such as Cupriavidus pauculus are emerging as opportunistic pathogens of interest [14] with multiple case reports of infection in immunocompromised [15][16][17][18][19] and immunocompetent [20][21][22][23] people as well as in those with cystic fibrosis [24][25][26], with evidence of nosocomial transmission [27][28][29]. A comprehensive summary of bacteraemia caused by Cupriavidus species reported that C. pauculus accounted for the vast majority (87 %) of 23 reported cases across different countries [28].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mcr-5 has been detected in a Cupriavidus sp. closely related to C. gilardii isolated from the blood of an immunocompromised patient in South Korea ( 15 ).…”
Section: Observationmentioning
confidence: 99%
“…C. gilardii is gaining increasing attention as an emerging pathogen, and several studies have reported its role in human infections, including perirectal inflammation, bloodstream infection, muscular abscess, and catheter sepsis ( 15 ). In terms of antibiotic resistance, it has been suggested that C. gilardii is intrinsically resistant to ertapenem, meropenem, ampicillin, amoxicillin-clavulanate, gentamicin, tobramycin, and streptomycin, while it is susceptible to imipenem and cefotaxime and intermediately resistant to spectinomycin ( 9 ).…”
Section: Observationmentioning
confidence: 99%
“…With rapid advances in next-generation sequencing (NGS) and third-generation sequencing (TGS) technologies, the cost of whole-genome sequencing has declined rapidly (Abdallah et al, 2019, Lin andHsu 2020). The whole-genome sequencing of many plants species has been achieved, laying a foundation for genetic research and molecular breeding and providing an opportunity to discover the genetic determinants of phenotypical traits (Lincoln 2012, Delsuc and Tilak 2015, Yano et al, 2016, Fontana et al, 2020, Kweon et al, 2020, Nouws et al, 2020, Regalado et al, 2020, Shahraki et al, 2020. For species without reference sequenced genomes, developing SSR molecular markers based on a genomic survey is considered as an efficient strategy (Zhou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%